Strategic hybridity: National modernization and cultural security in Kazakhstan and Kyrgyzstan - Gappassova, A.G.; Anlamassova, Y.Zh.; Mambetova, A.I.; Abdildina, Kh.S. (NLC «Karaganda National Research University named after acad. Ye.A. Buketov», 2025)
This article provides a philosophical analysis of cultural security in Kazakhstan and Kyrgyzstan under the conditions of globalization, introducing the concept of “strategic hybridity”. The study critically examines the application of the theories of homogenization, glocalization, and hybridization. It demonstrates that none of these paradigms, taken in isolation, can fully capture the complex cultural dynamics of the region; rather, their dialectical interplay becomes evident. The phenomenon of “McDonaldization” is shown to encounter axiological resistance from local traditions of hospitality and social practices. Glocalization is analyzed as a process manifested in cultural initiatives aimed at constructing a national brand. “Strategic hybridity” is conceptualized as the conscious selection, adaptation, and recoding of global cultural forms in order to address the tasks of national modernization and reinforce renewed identity. The empirical basis includes comparative analysis of cultural strategies, patterns of digital media consumption, as well as case studies in music (Q-pop, KG-pop) and the fashion industry in both countries. The conclusion asserts that Kazakhstan and Kyrgyzstan are shaping a “third way” between Westernization and isolationism, transforming the resources of globalization into instruments of their cultural projects, thereby ensuring cultural security in the new era.
Social philosophy - Әлеуметтік философия - Социальная философия
Keywords: globalization; cultural security; national modernization; homogenization; hybridity; glocalization; identity; strategic hybridity; Kazakhstan; Kyrgyzstan